Evolution, Ecology, and Zoonotic Transmission of Betacoronaviruses: A Review - Jelinek, Herbert F.; Mousa, Mira; Alefishat, Eman; Osman, Wael; Spence, Ian; Bu, Dengpan; Feng, Samuel F.; Byrd, Jason; Magni, Paola A.; Sahibzada, Shafi; Tay, Guan K.; Alsafar, Habiba S. (Frontiers in Veterinary Science, 2021)
Coronavirus infections have been a part of the animal kingdom for millennia. The difference emerging in the 21st Century is that a greater number of novel coronaviruses are being discovered primarily due to more advanced technology and that a greater number can be transmitted to humans, either directly or via an intermediate host. This has a range of effects from annual infections that are mild to full-blown pandemics. This review compares MERS, SARS-CoV and SARS-CoV-2 in terms of similarities and differences in phylogenetic associations and zoonotic potential. The role of bats as possible host species and possible intermediate hosts including pangolins, civets, mink, birds’ other mammals are discussed with reference to receptor binding domains, zoonoses and reverse zoonoses. The review concludes with comments on ecological, social, cultural and environmental factors that may play a role and need to be considered with reference to possible future zoonotic events.